2022
DOI: 10.3390/ijms232012561
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neuroglial Apoptosis and Neuroinflammation in the Epileptic Focus of the Brain and in the Blood of Patients with Drug-Resistant Epilepsy

Abstract: Neuroglial apoptosis and neuroinflammation play an important role in epileptogenesis. The aim of this study is to evaluate neuronal and glial apoptosis in association with neuroinflammation in brain epileptic focus and inflammatory changes in blood in patients with focal drug-resistant epilepsy (DRE). Pathological changes in the temporal lobe in epilepsy (histology, transmission electron microscopy), levels of apoptotic and neuroinflammatory proteins: active caspase-3 (immunohistochemistry), full-length form c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Previous studies have found that epilepsy is closely related to apoptosis, but the mechanisms involved are not yet fully understood ( Sokolova et al, 2022 ). The current study speculates that the mechanism may be closely related to the development of neuroinflammation and the elevation of pro-inflammatory factors (TNF-α, NF-kB, IL-1β and IL-6) ( Fuller et al, 2020 ; Sah et al, 2021 ; Yamanaka et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that epilepsy is closely related to apoptosis, but the mechanisms involved are not yet fully understood ( Sokolova et al, 2022 ). The current study speculates that the mechanism may be closely related to the development of neuroinflammation and the elevation of pro-inflammatory factors (TNF-α, NF-kB, IL-1β and IL-6) ( Fuller et al, 2020 ; Sah et al, 2021 ; Yamanaka et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…From our previous results, it can be seen that in the cortex of the temporal lobe of DRE patients, neuroinflammatory processes occur, including a high expression of TNF- α and FAS by immunocompetent cells of the nervous tissue. In the white matter, these processes are also present but less intense [ 13 ]. At the same time, there is the previously shown increased lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation in epilepsy foci, which is combined with the development of glioneuronal apoptosis, affects angiogenesis and BBB permeability and creates conditions for the development of drug resistance and the progression of epilepsy [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that neuroinflammation plays a key part in epileptogenesis [ 21 , 22 ]. In turn, it affects other processes such as neurogenesis and leads to abnormal reorganization of neuronal networks, mainly in the hippocampus, further promoting neuronal death [ 23 , 24 , 25 ]. Consequently, inhibiting neuroinflammation may be effective for the reduction or even prevention of epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%